The Influence of Inaportnet on the Effectiveness of Clearance In/Out Ships at PT Oremus Bahari Mandiri Surabaya - Nugraha, Markus Asta Patma; Alwin, Alwin (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
This study aims to determine the effect of Inaportnet on the effectiveness of ship entry and exit permits at PT Oremus Bahari Mandiri Surabaya. Data collection was carried out at PT Oremus Bahari Mandiri Surabaya in June 2019 by means of observation, study documentation, and distributing questionnaires. The collected data was processed using simple linear regression analysis techniques, validity test, reliability test, and coefficient of determination. The results showed that Inaportnet at PT Oremus Bahari Mandiri Surabaya has been running well with an R2 value of 0.804 or 80.4% Inaportnet has an effect on the effectiveness of Clearance in/out Ships at PT Oremus Bahari Mandiri Surabaya.